Essential Arginyl Residue at the Active Site of Pyrophosphate:Fructose 6-Phosphate 1-Phosphotransferase from Potato (Solanum tuberosum) Tuber. - Montavon, P; Kruger, N (1993)
The aim of this work was to test the proposal that the active site of pyrophosphate:fructose 6-phosphate 1-phosphotransferase (PFP) contains an essential arginyl residue. Enzyme activity was inhibited equally in the glycolytic and gluconeogenic directions by arginine-modifying reagents. The second-order rate constants for 2,3-butanedione and phenylglyoxal were 13.1 [plus or minus] 0.45 and 55.3 [plus or minus] 1.3 M-1 min-1, respectively. The corresponding values for the kinetic order of inactivation by these modifying reagents were 0.84 [plus or minus] 0.049 for 2,3-butanedione and 0.89 [plus or minus] 0.052 for phenylglyoxal. The substrates, fructose 6-phosphate and pyrophosphate, and a range of substrate analogs protected the enzyme from inactivation by 2,3-butanedione. These data suggest that modification of no more than one arginyl residue at, or close to, the active site is required to inhibit the enzyme. This result supports the proposal that the active site of PFP in plants is equivalent to that of the bacterial ATP-phosphofructokinase (S.M. Carlisle, S.D. Blakeley, S.M. Hemmingsen, S.J. Trevanion, T. Hiyoshi, N.J. Kruger, and D.T. Dennis [1990] J Biol Chem 265: 18366-18371).